KONDISI GEOLOGI DAERAH RUTENG DITAFSIR PADA DATA GAYA BERAT - Tatang Padmawidjaja (Jurnal Geologi dan Sumberdaya Mineral, 2010)
Ruteng Area was occupied by the gravity anomaly values between 60 to 160 mgal, showing high anomaly between 100 to 160 mgal and basin anomaly indicated by gravity values between 60 to 100 mgal. The high anomalies are associated with a shallow or exposed basement consisting of Kiro Formation. Wuas Basin is interpreted as intermountain basin, meanwhile basins from Ruteng to the southern part are controlled by faults, and the high anomalies at the southern part is presumed to be granodiorite (Tmg). The sedimentary rocks filling the basins are Nangapanda and Bari Formations. Based on the lineament, there are some faults involving Ruteng, Ulumbu, Pocodedeng and Bajawa Faults. AB geological model of the gravity anomaly cross section shows two layer, consisting of lower layer (basement) with density of 2.71 gr/cm3, the second layer is sedimentary rocks with density of 2.6 gr/cm3. Ruteng, Ulumbu, and Pocodedeng faults controlled the swallowing magma of which can function as a heat source of the geothermal system at the studied area.Keywords : gravity anomaly, lithology, faults, geothermal, Ruteng area.